2020
DOI: 10.1016/j.bbamem.2020.183415
|View full text |Cite
|
Sign up to set email alerts
|

Penetratin translocation mechanism through asymmetric droplet interface bilayers

Abstract: Penetratin is a cell penetrating peptide (CPP) that can enter cells by direct translocation through the plasma membrane. The molecular mechanism of this translocation still remains poorly understood. Here we provide insights on this mechanism by studying the direct translocation of the peptide across model membranes based on Droplet Interface Bilayers (DIBs), which are bilayers at the interface between two adhering aqueous-in-oil droplets. We first showed with symmetric bilayers made of a mix of 1-palmitoyl-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 37 publications
(37 reference statements)
0
27
0
Order By: Relevance
“…For instance, such a membrane recruitment-based mechanism promotes the translocation of amphipathic peptides. 15,54 However, C2/C2m showed inconsistent behaviors (Figure 6d), as their permeation rates were not reflected by the irinterfacial recruitment (except if C2m was considered alone). This observation indicates that the capacity of a peptide to insert into the bilayer membrane represents only one parameter controlling permeability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, such a membrane recruitment-based mechanism promotes the translocation of amphipathic peptides. 15,54 However, C2/C2m showed inconsistent behaviors (Figure 6d), as their permeation rates were not reflected by the irinterfacial recruitment (except if C2m was considered alone). This observation indicates that the capacity of a peptide to insert into the bilayer membrane represents only one parameter controlling permeability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Their membrane recruitment was likely mediated by the hydrophobic residues in the peptides (L, Y) , and the methylation at the leucine could improve their orientation and interaction with the membrane. For instance, such a membrane recruitment-based mechanism promotes the translocation of amphipathic peptides. , …”
Section: Resultsmentioning
confidence: 99%
“…Penetratin also tends to form peptide-rich regions at the surface of PG liposomes . Finally, PG appears as a permissive lipid for direct translocation across pure lipid membranes. ,,, As opposed to PG, PS is a biologically relevant lipid when investigating internalization mechanisms of CPPs, but it has been scarcely used. Penetratin has a higher affinity for PS-containing membranes than just PC and adopts an α-helical structure in its presence .…”
Section: Discussionmentioning
confidence: 99%
“…Penetratin has a higher affinity for PS-containing membranes than just PC and adopts an α-helical structure in its presence . Regarding direct translocation, the role of PS is not clear, as it was shown to allow direct translocation or not, depending on the experimental setup. Interactions of Penetratin with model membranes incorporating PI­(4,5)­P 2 have never been studied, though it was shown that direct translocation could occur in liposomes composed of PC, PI, and PI-phosphates …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation